Brief Report: A Pilot Summer Robotics Camp to Reduce Social Anxiety and Improve Social/Vocational Skills in Adolescents with ASD. - Kaboski, Juhi; Diehl, Joshua; Beriont, Jane; Crowell, Charles; Villano, Michael; Wier, Kristin; Tang, Karen (Journal of Autism & Developmental Disorders, 2015)
This pilot study evaluated a novel intervention designed to reduce social anxiety and improve social/vocational skills for adolescents with autism spectrum disorder (ASD). The intervention utilized a shared interest in robotics among participants to facilitate natural social interaction between individuals with ASD and typically developing (TD) peers. Eight individuals with ASD and eight TD peers ages 12-17 participated in a weeklong robotics camp, during which they learned robotic facts, actively programmed an interactive robot, and learned 'career' skills. The ASD group showed a significant decrease in social anxiety and both groups showed an increase in robotics knowledge, although neither group showed a significant increase in social skills. These initial findings suggest that this approach is promising and warrants further study.